Blockchain and Applications International Congress - Prieto, Javier; Das, Ashok Kumar; Ferretti, Stefano; Pinto, António; Corchado, Juan Manuel (Advances in Intelligent Systems and Computing, 2020)
XIII, 180 p. 97 illus., 40 illus. in color.